Links for a common cultural identity in the Mediterranean Basin - Montserrat Bosch Gonzáles; Tiziana Campisi (Agathón)
The Mediterranean Sea can be considered the common link between all the Countries surrounding it. Different peoples, cultures, arts, crafts, religions and traditions have passed through it, forging both a shared cultural identity and also differences, which can be easily traced in a lot of cities and territories. The Mediterranean city suggests unions and dissonances, sealing the alliance pact that has seen peaceful coexistence, albeit after the imposed dominations of a multi-ethnic and multicultural society. Many cities overlooking the Mediterranean Sea, as Barcelona, Palermo and Skikda, still today impose a reflection about how is strong the evident relation between their different ways of living. We also want to associate the shared creation – through the European Erasmus+ project, K2 action, entitled Smart Rehabilitation 3.0 – of a common professional profile in Building Rehabilitation Expert, as a model of rehabilitation and safeguard for historic Mediterranean cities.